2002
DOI: 10.1111/j.1530-0277.2002.tb02568.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Healing and Bone Mass in Rats Fed on Liquid Diet Containing Ethanol

Abstract: This study showed that rats fed on a diet mixed with ethanol have a histologically delayed fracture healing associated with decreased bone density and mineral content. Besides the negative effects of ethanol on bone metabolism, it also interferes with the fracture-healing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Up to 40% of orthopedic trauma patients admitted to the emergency department have elevated blood alcohol levels (Levy et al, 1996; Savola et al, 2005), suggesting that alcohol abuse may increase the risk for traumatic orthopedic injury. Clinical studies have found that while alcohol abuse also increases the risk for a non‐healing fracture injury (Chakkalakal, 2005; Elmali et al, 2002; Nyquist et al, 1997), the cellular and molecular mechanisms underlying alcohol consumption‐related fracture nonunion have not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 40% of orthopedic trauma patients admitted to the emergency department have elevated blood alcohol levels (Levy et al, 1996; Savola et al, 2005), suggesting that alcohol abuse may increase the risk for traumatic orthopedic injury. Clinical studies have found that while alcohol abuse also increases the risk for a non‐healing fracture injury (Chakkalakal, 2005; Elmali et al, 2002; Nyquist et al, 1997), the cellular and molecular mechanisms underlying alcohol consumption‐related fracture nonunion have not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of Wnt signaling due to alcohol exposure could be another mechanism of impairment of MSC differentiation, and an incomplete healing process persists up to two weeks post-fracture [127]. Chronic alcohol exposure had an effect on fracture healing with decreased mineralization, as reported in different experimental studies [128][129][130]. Testing the mineralization using alizarin red and perchloric acid staining as well as measuring osteoblast-specific genes, RUNX2, BGLAP and COL1A1, revealed that ethanol-treated MSCs had a significantly lower osteogenic capacity due to downregulation of the SIRT1 gene [131].…”
Section: Pre-clinical Studiesmentioning
confidence: 71%
“…DWB is commonly prescribed to patients deemed to be at higher risk of complications and the role of selection bias in producing our results must be considered. Factors known to increase rates of complications include older age [ 25 ], smoking [ 26 ], alcohol [ 27 ], diabetes mellitus (DM) [ 28 ], obesity [ 29 ], OTA 42C fractures [ 30 , 31 ] and open fracture [ 32 ]. Furthermore, it is possible that reamed nailing may minimise non-union [ 5 , 33 ], while the effect of dynamic nailing on union time and complication rates has produced mixed results [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%